Factors affecting the decision of cacao farmers in joining a cooperative in Subasta, Calinan District, Davao City - Arayan, Cyril Jane C.
The Philippines is one of the countries that produces cacao and the industry in the country steadily grows. The Subasta Integrated Farmers Multi-Purpose Cooperative (SIFMPC) is the only cooperative located in Subasta, Calinan District, Davao City which primarily engaged in cacao production. Knowing the several benefits of joining a cooperative such as a secured market for their products, there are still farmers who are non-members in the area. Thus, this study was conducted to identify significant factors that affect the monthly income from cacao farming as well as the decision of cacao farmers in joining a cooperative in Subasta. Through a structured questionnaire, primary data was collected from 104 cacao farmers in the study area and was then analyzed using descriptive analysis, ordinary least squares regression, and pro bit model. Results of the OLS showed that the factors affecting the monthly income of cacao farmers are the number of cacao trees, cooperative membership, types of fertilizer applied, age, years of formal education, and the application of fruits spray. On the other hand, results of the binary probit model showed that attendance of seminar/training from the Government, buyer of beans (cooperative or not), household size, and the farmer's main source of income are the factors affecting the decision of cacao farmers to join a cooperative. In terms of productivity and income of farmers, cooperative members are more productive and have higher income from cacao farming relative to non-members.